Struktur Kepribadian pada Aspek ID Tokoh Utama dalam Novel Di Balik Kabut Amnesia Karya Mira W. - ARTIFA SORRAYA; Anita Kurnia Rachman (IKIP Budi Utomo Malang, 2021)
Abstract: Novel is one of the literary genres. Novels are in great demand by various groups. One of them is written by a senior author, the novel by Wira. W. Wira. W one of the Indonesian female novelists. One of Mira's romance novels. W, which was published on November 18, 2019, is a novel entitled Behind the Fog of Amnesia. This novel tells the story of a woman who experiences dissociative amnesia. This disease occurs because of an incident that makes the child disappear. The main character has difficulty distinguishing between his imagination and his religious life. During the experience of dissociative amnesia, his reality life is influenced by his imagination, when in fact it is not what the main character thinks. Therefore, the researcher chose to analyze the Id aspect in the main character. This research is a descriptive qualitative study using the psychoanalytic approach of Sigmund Freud.